Historical Geographies of Coastal Tourism: Mossel Bay, South Africa c.1850-1988 - Rogerson, Jayne M.; Rogerson, Christian M. (Bulletin of Geography. Socio-economic Series, 2023)
During the past decade there has occurred a burst of international research and debate on coastal tourism as part of the ‘blue economy’ including a growth of geography-specific scholarship. Arguably, however, within the extant geographical literature there is an overwhelming ‘present-mindedness’ and limited historical perspectives. This paper addresses this neglected knowledge gap by using an historical approach and archival sources to undertake a locality-based study of the historical transitions which have shaped and reshaped one coastal settlement in South Africa. The Mossel Bay area is of considerable historical significance because of its long history of indigenous settlement before the first European contacts triggered by the arrival in 1488 of Bartholomew Diaz and crew who were in search for a trading sea route for Portugal to India. The nature of the colonial growth of tourism in Mossel Bay and the distinctive tourism economy of the town under apartheid is interrogated. This culminated in the scripting of the controversial 1988 Dias festival hosted to celebrate the opening of ‘apartheid’s last museum’ which occurred before Mossel Bay would experience a radical social transition following South Africa’s democratic elections. Overall, the evolutionary pathways and transitions in the historical geography of this coastal locality are the focus of discussion.